The Awareness of Generation Z About Nature, Sex and Gender - Siswati, Endah; Yefi Dyan Nofa Harumike; Fera Tara Batari (Universitas Islam Balitar, 2022)
The patriarchal culture that is socialized and internalized from generation to generation creates misunderstandings about the nature of men and women. This misunderstanding is also related to the confusion in the meaning of society about the concept of sex and gender. Efforts to straighten understanding and build public gender awareness have long been promoted. How is the result? How is the awareness or understanding of Generation Z about the concepts of sex and gender and the nature of men and women? This research was conducted to answer this question. The research method used is descriptive quantitative method. Researchers calculate, juxtapose and compare the percentage of respondents' answers, to draw concepts or conclusions with logical and critical analysis. The population of this study were social and political students at the Balitar Islamic University. The research sample was taken using quota sampling, and determined 100 male students and 100 female students as respondents. The results of this study indicate that: 1) respondents' awareness of the concept of sex or gender is classified as good, but respondents' awareness of the concept of gender is still below the average, 2) the majority of respondents are confused in distinguishing the concepts of sex and gender, and 3) the majority of respondents are wrong in interpreting the essential nature of men and women. This research can be used as a reference for government and non-government institutions in conducting socialization to build gender awareness of the younger generation. Keywords: feminism, gender awareness, patriarchy, women, men